On the structure of Leidniz algebras, whose subalgebras are ideals or core-free - Chupordia, V.A.; Kurdachenko, L.A.; Semko, N.N. (Доповіді НАН України, 2020)
An algebra L over a field F is said to be a Leibniz algebra (more precisely, a left Leibniz algebra), if it satisfies
the Leibniz identity: [[a, b], c] = [a, [b, c]] — [b, [a, c]] for all a, b, c ∈ L. Leibniz algebras are generalizations of
Lie algebras. A subalgebra S of a Leibniz algebra L is called core-free, if S does not include the non-zero ideal.
We study the Leibniz algebras, whose subalgebras are either ideals or core-free. Aлгебра L над полем F називається алгеброю Лейбніца (точніше, лівою алгеброю Лейбніца), якщо вона задовольняє таку тотожність Лейбніца: [[a, b], c] = [a, [b, c]] – [b, [a, c]] для всіх a, b, c ∈ L. Алгебри Лейбніца
являють собою узагальнення алгебр Лі. Підалгебра S алгебри Лейбніца L називається вільною від ядра,
якщо S не містить ненульових ідеалів. Розглянуто алгебри Лейбніца, усі підалгебри яких є ідеалами або
вільними від ядра.